Status and opportunities for improvement in greenhouse gas emission inventories for the cattle production in Latin America and the Caribbean region: A perspective - Ruden, Alejandro; Torres, Felipe; Berndt, Alexandre; Gómez, Carlos; Salazar, Francisco; Casallas, Ivon; Montenegro, Johnny; Ku-Vera, Juan Carlos; Manrique, María Lourdes; García Ascolani, Mariana; Alfaro, Marta; Cornejo, Paulo; et al. (2023)
The Intergovernmental Panel on Climate Change (IPCC) provides the reference for national greenhouse gas emission (GHG) inventories towards standardized, accurate, measurable, and comparable National Inventory Reports (NIR). For compliance with the 1.5⁰C commitments under the Paris Agreement, most countries have made efforts to improve their inventory methods to tier 2 or 3. However, some relevant activities within Latin American and the Caribbean (LAC) countries, such as enteric methane emissions and methane and nitrous oxide emissions from cattle manure management are still estimated using tier 1 methods, which leads to a high uncertainty due to the importance of livestock emissions in the national totals for these countries. In this context, reducing the uncertainty in GHG inventories would not only improve the accuracy of national reports but it would also provide solid baselines for national mitigation initiatives e.g., Nationally Determined Contributions under the Paris Agreement, and accurate tools to venture into carbon bonds or payments for ecosystem services. The aim of this study was to review the status of national GHG inventories specifically for these three cattle emission categories in 11 LAC countries. We conducted a survey of GHG inventory experts in the 11 LAC countries, to identify the potential for improvement and the main barriers to achieving this. Despite some initiatives, there is still a large potential for reducing the uncertainty in LAC national GHG emission estimates, the barriers to or solutions can be categorized as technical, policy, and institutional issues. However, improving the GHG inventories of LAC countries, specifically for cattle emissions, is feasible in the medium term, as long as multilateral actions are considered, coherently linked under a comparable and verifiable methodology and including a commitment by countries to invest public funds in relevant research and innovations.